The effect of polycaprolactone/graphene oxide electrospun scaffolds on the neurogenic behavior of adipose stem cells - ŞAHİN, ALİ; GÜNDÜZ, OĞUZHAN (Elsevier Ltd, 2022)
Stem cell destiny can be controlled with scaffold biomaterials in tissue engineering and regenerative medicine. This study aimed to investigate the neuronal differentiation potential of human adipose tissue-derived mesenchymal stem cells in graphene nanofiber matrix in vitro. Stem cell isolation was performed from adipose tissue taken from human by mechanical and enzymatic methods. The differentiation potential was examined after incubation of adipose stem cells in normal medium and neural differentiation medium, on graphene oxide (GO) and polycaprolactone (PCL) composite scaffolds produced by electrospinning technique. In vitro studies indicated that the presence of GO in PCL scaffold increases an effect on cell attachment, proliferation, infiltration into the scaffold, and neuronal differentiation. Also, unlike subcutaneous tissue, it has been shown immunohistochemically that mesenchymal stem cells derived from epidural adipose tissue tend to differentiate into oligodendrocytes. © 2022 Elsevier Ltd
Keywords: Adipose-derived stem cell; Electrospinning; Graphene oxide; Nanofiber scaffold; Neuronal differentiation; Polycaprolactone